KIF20A activated by transcription factor GATA2 promotes cell growth in hepatitis B virus-related hepatocellular carcinoma - Xu, Juan; Cheng, Wenhua; Wang, Yi; Zhou, Yunpeng; Wang, Zhiming; Dai, Yunyan; Li, Yaoxuan; Chen, Pinggui; Liu, Ting; Li, Yifan; Li, Gaopeng; Qu, Wenqing; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundElevated evidence suggests that KIF20A plays an important role in hepatocellular carcinoma (HCC) progression. Nevertheless, the underlying mechanism by which KIF20A promotes HCC cell growth are not well understood.MethodsUsing TCGA-LIHC RNAseq and GEO datasets, we assessed the KIF20A expression and patient survival in HCC and hepatitis B virus (HBV)-related HCC. Mutant and CNV analysis were performed to evaluate the genetic alteration of KIF20A in HCC. PPI network and GSEA enrichment was utilized for analyzing the KIF20A-related genes and involved pathways in HCC. To further explore regulatory mechanism in HBV-related HCC, PROMO prediction and luciferase reporter system was utilized for verifying HBx/GATA2/KIF20A binding sites. CCK-8 and flow cytometry were carried out to determine the regulation of GATA2-KIF20A on HBV-related HCC cell proliferation and apoptosis.ResultsKIF20A was significantly upregulated in pan-cancer (including HCC). KIF20A mRNA level was a significant independent predictor of overall survival in HBV-related HCC patients. Genetic alterations analysis revealed the copy number gain and amplification triggered KIF20A upregulation in HCC. In addition, the genes associated with KIF20A expression in HCC was enriched in PLK1 pathway and cell cycle in HCC. HBx might indirectly binds to KIF20A promoter via regulating GATA2. Additionally, transcription factor GATA2 directly binds to the promoter region of KIF20A. Overexpression of GATA2 promotes HepG2.2.15 cell growth and inhibits cell apoptosis via modulating KIF20A.ConclusionsOur findings demonstrated that HBx contributed to cell proliferation by interacting with GATA2 and KIF20A in HBV-related HCC.